IMPLEMENTASI PROGRAM CAPACITY BUILDING INDONESIA AUSTRALIA FISHERIES SURVEILLANCE FORUM DALAM PENANGGULANGAN ILLEGAL, UNREPORTED AND UNREGULATED (IUU) FISHING TAHUN 2017-2019 - Muhammad Rafi Ardin Darmawan (2022)
Indonesia, which is an archipelagic country, makes the marine area the vital points for economic life and security. Australia is one of the regional powers in the Pacific region making Indonesia as Buffer State. These two countries have a common goal to fighting IUU fishing. One way is through IAFSF collaboration and one of its programs is the Capacity Building.In this study, I used descriptive qualitative research to describe the implementation of Indonesia Australia''s capacity building program against IUU Fishing in 2017-2019 with data collection techniques, interviews and literature studies. I gets primary and secondary data and the Triangulation Technique as a Data Validity Technique.In implementing the capacity building program, the Indonesian Fleet learned about English, marine area surveillance tools, the theory of IUU Fishing surveillance and countermeasures, and how Australia responds to IUU fishing activities in their country. In addition, there are still inefficiencies in the implementation of capacity building programs. And this is an obstacle in handling IUU Fishing.The IAFSF capacity building program should be the program that has the most impact on combating IUU fishing in Indonesia, but the results of the program are still not evenly distributed.In tackling IUU Fishing, funds must be allocated to improve quality and quantity, in addition to holding outreach to the surrounding community related to IUU Fishing